2022
DOI: 10.1115/1.4054066
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Incoming Vortex and Wake on the Aerodynamics of an Intermediate Turbine Duct

Abstract: In a high bypass ratio aircraft engine, the high-pressure and low-pressure turbines are connected by an intermediate turbine duct (ITD). The aerodynamic performance of the ITD is affected by the incoming flow from the high-pressure turbine. This paper investigates the effects of an incoming wake or/and a near casing streamwise vortex on the flow field and loss of an ITD. For the case with only an incoming wake, the wake interacts with the boundary layer, forming a pair of vortices and causing additional loss. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…Liu et al [23] investigated the impact of a cavity blowing jet on the integrated AITD, and indicated that the cavity jet changed the pressure gradient from hub to casing and induced local separation on the hub just downstream of the cavity outlet. Zhou et al [24] studied the coupling effect of upstream wake and inlet streamwise vortex on the internal flow of the ITD, and pointed out that the distance between them has a major effect on the flow pattern and aerodynamic loss of the ITD. The authors' team [25,26] studied the influence of sweeping frequency and wake intensity on the inner stream of the integrated AITD and the boundary layer of the integrated LPT-GV, and indicated that as wake intensity decreases or the wake reduced frequency increases, the wake skewness increases and the wake width narrows, which can make the duration and radial range of the flow separation inhibition by wakes decrease, resulting in an increase in separation loss.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [23] investigated the impact of a cavity blowing jet on the integrated AITD, and indicated that the cavity jet changed the pressure gradient from hub to casing and induced local separation on the hub just downstream of the cavity outlet. Zhou et al [24] studied the coupling effect of upstream wake and inlet streamwise vortex on the internal flow of the ITD, and pointed out that the distance between them has a major effect on the flow pattern and aerodynamic loss of the ITD. The authors' team [25,26] studied the influence of sweeping frequency and wake intensity on the inner stream of the integrated AITD and the boundary layer of the integrated LPT-GV, and indicated that as wake intensity decreases or the wake reduced frequency increases, the wake skewness increases and the wake width narrows, which can make the duration and radial range of the flow separation inhibition by wakes decrease, resulting in an increase in separation loss.…”
Section: Introductionmentioning
confidence: 99%